Universal Credit and Crime - Rocco D'Este; Alex Harvey (Institute of Labor Economics (IZA), 2020)
We evaluate the criminogenic effects of Universal Credit (UC), a monumental welfare reform designed to radically change the social security payment system in the United Kingdom. We exploit the UC rollout across constituencies using monthly data from 2010 to 2019 for England and Wales. We find UC has caused around 45,000 burglaries, with criminogenic effects lasting until the end of the sample period and expected to grow considerably by the time UC is fully rolled out when 6.5 million more individuals will use the system. The analysis suggests the worsening of benefit recipients' financial conditions as the key mechanism.
Keywords: K14; K42; 330; universal credit; benefits; welfare system; crime